Isolation and characterization of plant growth promoting bacteria from wheat-sugarcane cropping system - Chandra, Priyanka; Chandra, Amaresh (Journal of Cereal Research, 2016)
An increasing demand for low-input agriculture has resulted in a greater interest in soil microorganisms which are able to enhance plant nutrition and health, and to improve soil quality. Microorganisms present in rhizosphere can be beneficial to plant by producing plant growth-promoting substances such as indole acetic acid (IAA),or being antagonist to pathogens by siderophore and HCN production or by increasing the availability of nutrients such as nitrogen, phosphorus, iron and zinc. Soil microorganisms not only have the capability to produce compounds that possess plant growth promoting activity which leads to high yield but also inhibit phytopathogens. Among the soil microorganisms, bacteria and fungi have received considerable attention as plant growthpromoters and biocontrol agents.